History of cartography : International symposium of the ICA, 2012 - Collier, Peter; Torok, Zsolt Gyozo; Liebenberg, Elri (Lecture Notes in Geoinformation and Cartography, 2014)
This volume collects 22 papers presented at the 4th International Symposium of the ICA Commission on the History of Cartography, held at Eötvös Loránd University, Budapest, Hungary, on 28-29 June 2012. The overall conference theme is 'Exploration - Discovery - Cartography', but preference has been given to papers dealing with cartography in the 19th and 20th centuries.  The papers are classified according to regional sub-themes, i.e. papers on the Americas, papers on Africa, etc.